Features of tertiarisation in the developed economies and worldwide offshoring - Maria Stella Chiaruttini (European Regional Science Association (ERSA), 2013)
In the last decades, the world economy has been undergoing a process of production reorganisation and relocation of unprecedented scale and scope. The era of ?globalisation? has been characterised by falling barriers to trade and increasing capital flows, both of speculative and investment nature. Huge trade deficits and surpluses have emerged, which have raised a renewed interest in international trade issues as well as concern within the scientific community, as is witnessed in the literature about global imbalances. Since the Nineties, few rich countries (United States, Great Britain, France, Japan, Switzerland, Germany and the Netherlands) have been securing a substantial stake in worldwide production through FDI, a phenomenon mirrored by increasing FDI negative positions for nations such as China, Mexico, Brazil and Ireland. The building up of this dualistic international structure can be detected also analysing the dynamics of net exports of royalties and license fees. This fact might suggest a new perspective from which to study the rise of the ?tertiary economy?, which could then be considered as ?post-industrial? having offshored manufacturing production, while paying for the imports of goods with the profit stream accruing from FDI, the sale of property rights and the exports of other sophisticated services. This interpretation, however, would explain the recent development path of only a subset of FDI net exporter countries, namely the US, Great Britain, France and, partially, Japan, whereas Germany, Switzerland and the Netherlands are running a growing merchandise trade surplus. This heterogeneity calls for further investigation. The paper therefore, combining information from trade flows and net asset positions worldwide and their evolution since the Seventies-Eighties, proposes a tentative classification of countries based on their relative strength in manufacturing and several services categories so as to identify, among them, a core and a periphery in the chain of worldwide production. To do that several indicators are considered, such as each country?s comparative advantages, its dependence on net exports and its market share in the world economy by relevant trade category. The picture resulting is that of a growing specialisation among advanced as well as emerging economies. Paradigmatic examples of this heterogeneity are the United States, increasingly involved in financial activities, vis-à-vis the export-driven Germany, or the industrial producer China and the offshoring of services towards India.
Keywords: F02; F14; F54; F63; O14; 330; offshoring; international trade; global imbalances; tertiarisation; structural change